Hydroxyl radical mediated DNA base modification by manmade mineral fibres. Issue 7 (July 1989) - Leanderson, P; Söderkvist, P; Tagesson, C
Abstract : Manmade mineral fibres (MMMFs) were examined for their ability to hydroxylate 2-deoxyguanosine (dG) to 8-hydroxydeoxyguanosine (8-OH-dG), a reaction that is mediated by hydroxyl radicals. It appeared that (1) catalase and the hydroxyl radical scavengers, dimethylsulphoxide and sodium benzoate, inhibited the hydroxylation, whereas Fe2+ and H2O2 potentiated it; (2) pretreatment of MMMFs with the iron chelator, deferoxamine, or with extensive heat (200-400 degrees C), attenuated the hydroxylation; (3) the hydroxylation obtained by various MMMFs varied considerably; (4) there was no apparent correlation between the hydroxylation and the surface area of different MMMFs, although increasing the surface area of a fibre by crushing it increased its hydroxylating capacity; and (5) there was good correlation between the hydroxylation of dG residues in DNA and the hydroxylation of pure dG in solution for the 16 different MMMFs investigated. These findings indicate that MMMFs cause a hydroxyl radical mediated DNA base modification in vitro and that there is considerable variation in the reactivity of different fibre species. The DNA modifying ability seems to depend on physical or chemical characteristics, or both, of the fibre.